Synthesis of Substituted Oxazoles from N‐Benzyl Propargyl Amines and Acid Chlorides. Issue 21 (6th June 2013) - v. Wachenfeldt, Henrik; Paulsen, Filip; Sundin, Anders; Strand, Daniel
Abstract: The reaction between N ‐benzylpropargylamines and acid chlorides at elevated temperatures provides efficient, direct access to a variety of di‐ and tri‐substituted oxazoles. The versatility of this reaction is explored and 21 examples are demonstrated. The usefulness of the methodology is showcased through the short and efficient formal syntheses of medicinally relevant drugs aleglitazar and romazarit. Abstract : The reaction between N ‐benzylpropargylamines and acid chlorides at elevated temperatures gives oxazoles in up to 99 % yield. Twenty‐one examples are demonstrated varying the substitution at all positions of the heterocycle.